Band Alignment of Al2O3 Layer Deposited NO and SO2 Exposed (001) H‐Diamond Heterointerfaces Studied by Synchrotron Radiation X‐Ray Photoelectron Spectroscopy. Issue 22 (26th July 2018) - Saha, Niloy C.; Takahashi, Kazutoshi; Imamura, Masaki; Kasu, Makoto
Abstract : The interfacial energy band alignment of the interface between H‐terminated diamond, exposed to either NO or SO2, and an Al2 O3 layer is studied using synchrotron radiation X‐ray photoelectron spectroscopy (XPS) and X‐ray absorption near‐edge structure (XANES) measurements. From the results, type II band alignment is determined for both the Al2 O3 /NO/H‐diamond and the Al2 O3 /SO2 /H‐diamond heterointerfaces. The valence band offsets are determined to be 3.7 eV for the Al2 O3 /NO/H‐diamond heterointerface and 3.5 ± 0.1 eV for the Al2 O3 /SO2 /H‐diamond heterointerface. XPS spectra indicate that the NO and SO2 decompose on the H‐diamond surface, and XANES measurements demonstrate the formation of oxygen related interface states. Abstract : Exposure of NO and SO2 respectively to H‐diamond surface increase sheet hole carrier concentration. Energy band‐alignment and interfacial electronic states of Al2 O3 /NO/H‐diamond and Al2 O3 /SO2 /H‐diamond are investigated using XPS measurements and valence band‐offset of 3.7 and 3.5 ± 0.1 eV are determined. Oxygen‐derived interface states is confirmed from the XANES measurements in both cases.